THE FOUNDATION OF ALL PROFESSIONS - Allaniyazov, Ismail Begzhanovich; Ismaylova, Aziza Saadatdinovna (SCIENCE and SOCIETY, 2026)
The article is dedicated to the social significance of the teaching profession, with substantiated facts presented.